The Importance of the Venue Selection in an Event Organization Case Study: Special Event Organization Rencontre Alumni Entreprise 1 & 2 - Ardani, Edvi Gracia (E-Journal of Tourism, 2017)
The MICE industry in Indonesia has been growing fast in Indonesia. There are so many different ways to organize events from the planning to the evaluation. However, the determination of venue remains a very interesting issue to be studied. The success of event organization may be based on the venue selection. This study is aimed to examine the venue management in the special event management of the First and Second Rencontre Entreprise-Alumni (REA). The objective of the study is to find out the importance of the venue selection in the impact of the success of the event. Thus, selecting an event venue will require identifying physical resources present in the location. The method of the research is descriptive using the participant observation and in-depth interview as data collection procedure. The sampling design is judgment sample with the most productive sample who are the exhibitors who was in the first only or the second only of REA, and in both events. The research gives a quite significant result to the event owner to improve the next event organization. All aspects must have been well thought including the attendees management to which the venue selection influenced the most. The event owner was taking the most important part in the venue selection that was very lightly taking the attendees’ needs into consideration. The transportation would also take the biggest part of attendees’ problem in accessing the venue.
Keywords: special event; venue management; site selection; event management; tourism and hospitality industry; MICE